How Familiar are You With Your Identity? - Ahmed, Anjum; Fatima, Murshida (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
A change in the attitude of the society is a prerequisite for bringing about any substantial change in the status of women in the society. Since the role of women is most important and no nation can afford to ignore it. It becomes imperative to look into the fact that how women identify themselves as feminist. The present study is a descriptive survey to measure the feminist identity among prospective teachers. The purposive random sample consisted of 100 female prospective teachers. The sample was categorized into two groups, i.e. entrant and proficient groups. The major findings of the study were that in both the entrant and proficient groups the art streams respondents scored the highest average feminist identity than the science group this could mean the subjects taught in arts gives more opportunity to students to learn about their identity in the social patriarchal system. It was also concluded that the art stream respondents may be at the „embeddendness-emanation stage‟ where a woman immerses herself in cultural and intellectual contexts that are woman oriented. Unlike the science stream respondents, which may be transiting from the earlier stage „passive acceptance stage‟ to „embeddedness–emanation stage‟.